Anti-dumping, Intra-industry Trade and Quality Reversals - Jose Luis Moraga-Gonzalez; Jean-Marie Viaene (Tinbergen Institute, 2004)
We examine an export game where two firms (home and foreign), located in two differentcountries, produce vertically differentiated products. The foreign firm is the most efficientin terms of R&D costs of quality development and the foreign country is relatively larger andendowed with a relatively higher income. The unique (risk-dominant) Nash equilibrium involvesintra-industry trade where the foreign producer manufactures a good of higher quality thanthe domestic firm. This equilibrium is characterized by unilateral dumping by the foreignfirm into the domestic economy. Two instruments of anti-dumping (AD) policy are examined,namely, a price undertaking (PU) and an anti-dumping duty. We show that, when firms' costasymmetries are low and countries differ substantially in size, a PU leads to a quality reversalin the international market, which gives a rationale for the domestic government to enact ADlaw. We also establish an equivalence result between the effects of an AD duty and a PU.
Keywords: F12; F13; 330; anti-dumping duty; intra-industry trade; price undertaking; product quality; quality reversals; Antidumping; Intraindustrieller Handel; Spieltheorie; Produktqualität; Theorie